أهمية استخدام بطاقة التقييم المتوازن للأداء في المصارف (دراسة تطبيقية في المصرف العقاري السوري) - القاضي, حسين; العمار, رضوان; الزرير, رانيا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research tries to define the Balanced Scorecard (BSC), explain its implementation mechanism, and show its importance and contribution to the transformation of the organization strategy into a common language understood by all its individuals. In so doing, it provides a clear, inclusive, and immediate image about the performance of the organization, translating the strategy into definite objectives, measures, targeted standards, initiatives for continuous improvement. This research also seeks to know how far the Syrian Real Estate Bank uses the perspectives measures of Scorecard to evaluate its performance. To achieve that, three hypotheses were formed, and a questionnaire was designed and analyzed by (SPSS) to test these hypotheses. This research has reached many results and recommendations, the most important of which is the necessity of implementing BSC in an integrated way in the Syrian Real Estate Bank by developing the current traditional measuring standards used by the bank. This practice can then be adopted by other banks in Syria.